2014
DOI: 10.1016/j.bmhimx.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Efectos adversos de la marihuana en la edad pediátrica: su conocimiento ¿podría limitar la legalización de la droga en México?

Abstract: A reflection on whether to expose, determine and clarify the effects of marijuana on pregnant adolescents and their fetus is a determining factor to consider more judiciously the tendency to legalize marijuana in Mexico. We emphasize alterations in the central nervous system, immune system and some genetic aspects of the fetus and its potential expressions at different stages of a child's life. Should pediatricians and parents allow, in addition to the difficulties that their patients and children face today, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…[26][27] It is difficult to predict all the damage that this drug produces in childhood, studies have reported that if its consumption is at an early age, there is more risk of brain regions damage with negative consequences on brain functions. 28 The most evident are its cumulative effects that hinder learning. 29 A little less than half of students (44%) do not perceive harm if people try marijuana once or twice, but a little less than one-third (28.7%) believe that if people regularly smoke marijuana they would be exposed to physical harm or others.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27] It is difficult to predict all the damage that this drug produces in childhood, studies have reported that if its consumption is at an early age, there is more risk of brain regions damage with negative consequences on brain functions. 28 The most evident are its cumulative effects that hinder learning. 29 A little less than half of students (44%) do not perceive harm if people try marijuana once or twice, but a little less than one-third (28.7%) believe that if people regularly smoke marijuana they would be exposed to physical harm or others.…”
Section: Discussionmentioning
confidence: 99%